Assessment of knowledge and attitude about child abuse amongst parents visiting a tertiary care hospital in Bengaluru, India - Shankar, Poornima; Agrawal, Avinash; K., Akash B.; Kumar, Mansi (International Journal of Contemporary Pediatrics, 2020)
Background: Child abuse is one of the problems in our society which still needs to be highlighted for general public in our country. It is a pressing human right issue and public health concern and the efforts to assess the awareness and mass education is very limited. Current study aimed to access knowledge and attitude for child abuse among parents attending a tertiary care hospital. Methods: The study was conducted amongst parents visiting pediatric OPD at Kempegowda institute of medical sciences, Bengaluru. Total 200 Parents were required to answer a series of questionnaire and then was statically analyzed. Results: It was seen that majority of parents lack knowledge regarding child abuse, 25% of parents believe that child abuse is just sexual violence, 23% parents thought that stubborn children can only be handled by physical punishment, 46% parents believed that only a girl child can be a victim of sexual abuse and only 19% had firm belief that boys can also be victim, 45% of parents believed that it is necessary to discuss with the child before making important decision concerning them, 35% parents were against the corporal punishment. Conclusions: There is a need to evolve strategies to protect the children from abuse and the measures should address both boys and girls and minimize impact.